The bioherbicidal potential of hemlock water extracts - Jovanović Vladan D.; Stanojević Stefan R.; Dmitrović Slavica S.; Nestorović-Živković Jasmina M.; Nikolić Bogdan R.; Dragićević Ivana Č.; Giba Zlatko S. (Archives of Biological Sciences)
Studying plant species rich in bioactive compounds, including allelochemicals, could lead to the development of biodegradable and environmentally safe herbicides. In this study, a water extract of hemlock (Conium maculatum L.), known to be rich in alkaloids, was used to investigate its effects on the germination of Amaranthus retroflexus L., Ambrosia artemisiifolia L., Stellaria media (L.) Vill., and Lactuca sativa L., providing valuable insights into its phytotoxic properties. Among the C. maculatum water extracts (CmWEs) tested, that of dry leaves showed the strongest inhibitory effect on the germination of all species analyzed. The CmWE of dry leaves (50%) completely inhibited seed germination of all species tested. The CmWE of dry stems (50%) reduced seed germination in S. media, A. retroflexus, and A. artemisiifolia by 20% to 89%, whereas the germination of L. sativa was less affected (9%). In addition, a CmWE of dry stems (5%) selectively inhibited ragweed germination (45%), while the germination of Lactuca sativa was not significantly affected. The CmWE of dry leaves (20%) inhibited early root and shoot growth of S. media more effectively than suppressing seed germination. Moreover, the dry leaves and inflorescences of C. maculatum demonstrate strong allelopathic properties even after two years of storage, highlighting the long-term potential of C. maculatum as a source of natural herbicides.